Major Problems in Analyzing Transitivity: A Case from Indonesia - Sri Harto; Sri Handayani (Universitas Widyatama, 2019)
This research applied a descriptive qualitative method to identify the major problems encountered by students in analyzing transitivity. It also aims to find out some of the alternative solutions to the students